EFETIVIDADE DO ENSINO DE EDUCAÇÃO AMBIENTAL: Um estudo de caso no Instituto Federal de Educação, Ciência e Tecnologia Fluminense campus Campos dos Goytacazes-Centro. - Carneiro, Eliane Paravidino (2013)
This paper seeks to investigate, understand and analyze if the environmental perception and awareness that underlie consciousness and the future actions of the individual are associated with the degree of formal environmental education the person receives. The environmental issues in formal education affect the whole person and should provide, to the student, the perception that not only raises awareness, but mainly that aware to change their attitudes and provide new knowledges and interests about not only local and regional environmental problems, such as those affecting the world. In this sense, a diagnosis was made, through the case study methodology of a qualitative nature with extensive literature review done in the Scielo, the portal Capes in Scopus using the key words: environment and environmental education and in other sources specific literature, with a questionaire and subsequent data analysis in order to investigate the effectiveness of the teaching of environmental education in the perspective of building a critical view on Environment and influence in everyday praxis of social actors in Higher Education of Industrial Maintenance Technology, Federal Institute of Education, Science and Technology Fluminense campus Goytacazes Campos/RJ/Center.